INTEGRATED AUDITS: CURRENT SITUATION IN NICARAGUA - Porras Rodríguez, Davis A.; Internos de Nicar, Instituto de Auditores (Nexo Revista Científica, 2014)
Integrated audits have quickly emerged in the different audit’s units because of the benefits it provides to organizations. Institutions that regulate the profession of auditing and senior management of different organizations began recommending integrated approach in order to evaluate with holistic approach all business processes’ risks and controls. The estate of the art of integrated audits was known through a structured survey, which was based on the theory established by the Information Systems Audit and Control Association (ISACA). Some activities were categorized under an integral approach, not integrated as expected, however, the research provides information in order to clarify both terms; Based on this clarification, many audit’s professionals can make adjustments to their internal processes and maintain the integrated approach. A new integrated audit concept was proposed in order to act as a reference to achieve the integrated approach. DOI: http://dx.doi.org/10.5377/nexo.v27i01.1440